Study of Mechanical Strength of Composite Materials Made from Marble and Sago Fiber Waste for Rencong Marble Souvenirs Storage - Ihsan Anwar; Asbahrul Amri; Lindawati Lindawati; Sandika Putri Rahayu; Edi Saputra (Politeknik Negeri Lhokseumawe, 2023)
Kedai Kandang Village, South Kluet District, South Aceh Regency, is one of the sago-producing areas. In this study, the waste resulted from the processing of sago was used as a reinforcing material for composite materials. This research was conducted to determine the mechanical strength of the composite made from marble waste reinforced with sago fiber waste to be used as rencong Marble souvenir storage. The composition of the mixture in the samples used was 85:10:5, 80:10:10, 90:7.5:2.5, and 80:12.5:7.5. The mechanical strength was determined through tensile strength testing. The results of the tensile test showed that the highest tensile strength values were shown in the sample with the percentage composition of a mixture of resin, marble powder, and sago fiber, 85:10:5. The average maximum stress value obtained is 18.707 N/m². The average modulus of elasticity obtained is 1.462 N/m².